Reconstruction of Orbital Exenteration Defects with Cross-median Forehead Flaps - Baum, Sven H.; Al-Bayati, Mohammad; Mohr, Christopher; Pförtner, Roman (Facial Plastic Surgery, 2024)
The aim of this study was to examine the role of forehead flaps in the reconstruction of orbital defects after exenteration. Patients undergoing orbital exenteration and reconstruction using median forehead flaps from January 2002 to August 2019 were enrolled in this retrospective study. All the patients were evaluated for wound complications, functional results, and tumor relapse. In total, 105 patients completed the study. Twenty-nine complications in 24 of these patients were assessed. The most common complications were wound dehiscence (11%), partial necrosis of the flap (6%), and bleeding (4%). A major complication occurred in two patients (2%), necessitating surgical correction. Only one patient had a local relapse. Sixty patients received osseointegrated implants, and 58 of them were treated with facial prostheses. The follow-up periods ranged from 6 to 189 months. Thus, forehead flap reconstruction after exenteration is a reliable method with a low complication rate. This technique can be used for primary or secondary reconstruction, and excellent long-term functional results can be achieved. A relapse-oriented follow-up is certainly possible.
Keywords: forehead flap; orbital exenteration; reconstruction; complications; survival